Water Awareness in The Irung-Irung Tradition as Implementation of Water and Sanitation Management for the Community of Cihideung Village, West Bandung Regency - Fitriyani, Anindyta; Nurhalizah, Siti; Felisa, Salma G; Hardiyanti, Retno A (CSID Journal of Infrastructure Development, 2024)
The local wisdom that exists within a community plays a crucial role in influencing the thinking and conduct of the community. One local wisdom that contains a hydrological educational message that impacts community awareness in maintaining water hygiene and proper sanitation is the Irung-Irung Tradition by the people of Cihideung Village, West Bandung Regency. The objective of this study is to comprehensively examine and assess the components of water awareness within the Irung-Irung Tradition practiced by the people of Cihideung Village in the West Bandung Regency. This study involves a descriptive qualitative research design, including data collection methods such as interviews, observation, and literature review. The employed data analysis technique encompasses data reduction, data display, and conclusion. The findings of the study indicate that the element of water awareness in the Irung-Irung Tradition contained a philosophical meaning in the form of an expression of gratitude to God for a spring that never subsides, respect for the spirits of the ancestors, and strengthening the bonds of brotherhood among the residents of Cihideung Village. The Irung-Irung Tradition is an effort to enhance awareness and concern for the people of Cihideung Village about the urgency of water and sanitation management manifested in community service activities and cleaning springs and waterways. Therefore, the values in the Irung-Irung tradition are local wisdom that participates in realizing the sixth sustainable Development Goals (SDGs) related to water accessibility and proper sanitation.